Recent Advances in Chemistry and Biological Activity of 2,6-Diphenyl Piperidines - Yousif, Mahmoud N. M. (Mini-Reviews in Organic Chemistry, 2022)
The review discusses different methods for the preparation of 2,6-diphenyl-piperidin-4-one derivatives. 2,6-Diphenyl-piperidin-4-one is prepared from aromatic aldehyde and acetone in ammonium acetate. Reaction of 1-phenylsulfinylpropan-2-one or 1-(4-chlorophenylsulfinyl)propan-2-one, aromatic aldehyde and ammonium acetate gives a series of 2,6-diaryl-2,3-dihydro-1H-pyridin-4-one 6a,b. 4-Phenyl-2-amino-1,3-butadienes reacts with N-allyl benzaldimine through Diels-Alder reaction to afford 2,6-diphenyl-4-piperidinone derivative 7. Also, reactions of 2,6-diphenyl-piperdin-4-one are discussed. The reactions of the latter compounds can be on nitrogen atom or carbonyl function group or methylene group adjacent to the carbonyl group. In addition, different applications of 2,6-diphenylpiperidin- 4-one are summarized.
Keywords: biological activity